2017
DOI: 10.1038/nn.4536
|View full text |Cite
|
Sign up to set email alerts
|

Activity-induced histone modifications govern Neurexin-1 mRNA splicing and memory preservation

Abstract: Epigenetic mechanisms regulate the formation, consolidation and reconsolidation of memories. However, the signaling path from neuronal activation to epigenetic modifications within the memory-related brain circuit remains unknown. We report that learning induces long-lasting histone modifications in hippocampal memory-activated neurons to regulate memory stability. Neuronal activity triggers a late-onset shift in Nrxn1 splice isoform choice at splicing site 4 by accumulating a repressive histone marker, H3K9me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 42 publications
3
108
0
4
Order By: Relevance
“…Their members, including GATAD2A , display preferential expression in fetal brain development(Li et al, 2015) and in recent work has been implicated in SCZ through open chromatin(Fullard et al, n.d.). Further, p66α (mouse GATAD2A ) was recently shown to participate in memory preservation through long-lasting histone modification in hippocampal memory-activated neurons(Ding et al, 2017). SNP-heritability appears to be consistently shared across regions and chromosomes between these two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Their members, including GATAD2A , display preferential expression in fetal brain development(Li et al, 2015) and in recent work has been implicated in SCZ through open chromatin(Fullard et al, n.d.). Further, p66α (mouse GATAD2A ) was recently shown to participate in memory preservation through long-lasting histone modification in hippocampal memory-activated neurons(Ding et al, 2017). SNP-heritability appears to be consistently shared across regions and chromosomes between these two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering studies by Zisapel and colleagues showed that activation of cultured cortical neurons causes a dramatic, Ca 2+ -dependent exclusion of the Nrxn2 SS3 insert that depends on specific sequence motifs associated with the alternatively spliced exon (Rozic-Kotliroff and Zisapel, 2007; Rozic et al, 2013), consistent with the high degree of regional regulation of SS3 alternative splicing (Ullrich et al, 1995). Subsequent more extensive studies showed that SS4 is also regulated by neuronal activity (Ding et al, 2017). The regulation of neurexin alternative splicing at SS3 and SS4 by activity appears to be physiologically important since it can be observed in vivo, both as a consequence of fear learning (Rozic et al, 2011; Ding et al, 2017) and as a diurnally regulated process (Shapiro-Reznik et al, 2012).…”
Section: Neurexins: Form and Functionmentioning
confidence: 99%
“…Subsequent more extensive studies showed that SS4 is also regulated by neuronal activity (Ding et al, 2017). The regulation of neurexin alternative splicing at SS3 and SS4 by activity appears to be physiologically important since it can be observed in vivo, both as a consequence of fear learning (Rozic et al, 2011; Ding et al, 2017) and as a diurnally regulated process (Shapiro-Reznik et al, 2012). …”
Section: Neurexins: Form and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…MACS was run with the default parameters but with the shift size adjusted to 100 bp to perform peak calling 67 Biotechnology Information Gene Expression Omnibus (NCBI GEO) 72 repository under the accession number GSE139884. Additionally, public datasets for hippocampal H3K9me3 (GSM2460430) 73 , H3K9ac (GSM2415914) 74 and CTCF (GSM2228526) 75 ChIP-seq experiments were retrieved for integrated data analysis.…”
Section: Rna-seq Chip-seq and Atac-seq Data Analysismentioning
confidence: 99%